2007
DOI: 10.1136/thx.2006.070847
|View full text |Cite
|
Sign up to set email alerts
|

Effects on patients with asthma of eradicating visible indoor mould: a randomised controlled trial

Abstract: Background: It is not clear whether associations between respiratory symptoms and indoor mould are causal. A randomised controlled trial was conducted to see whether asthma improves when indoor mould is removed. Methods: Houses of patients with asthma were randomly allocated into two groups. In one group, indoor mould was removed, fungicide was applied and a fan was installed in the loft. In the control group, intervention was delayed for 12 months. Questionnaires were administered and peak expiratory flow rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 19 publications
(14 reference statements)
1
83
0
4
Order By: Relevance
“…The results of CHARISMA strengthen the generally positive findings of six recent randomised trials of interventions to enhance the indoor environment -one in the US, 12 three in the UK, 11,14,15 and two in New Zealand. 16,17 Although the six interventions were heterogeneous, all sought to enhance ventilation, or housing, or both.…”
Section: 11supporting
confidence: 61%
See 2 more Smart Citations
“…The results of CHARISMA strengthen the generally positive findings of six recent randomised trials of interventions to enhance the indoor environment -one in the US, 12 three in the UK, 11,14,15 and two in New Zealand. 16,17 Although the six interventions were heterogeneous, all sought to enhance ventilation, or housing, or both.…”
Section: 11supporting
confidence: 61%
“…[23][24][25] In particular, it was decided not to measure peak flow because of diurnal variation in readings, with the result that even a large sample size might not detect a difference. 15,17 To count mould spores in children's bedrooms, or to measure their sensitisation to such spores, was also beyond the scope of this pragmatic study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Other studies have shown that remediating the water damage and mold in asthmatics' homes resulted in improvements in their health. 3,4 Therefore, accurate assessment of the molds in homes may be critical in evaluating asthma trigger concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…52 Remediation of mold has been shown to reduce symptoms and medication use in several populations, and its effects may not depend on whether the population is sensitized to mold. 55,56 The evaluation of a patient with persistent asthma includes an assessment of sensitization to the major indoor molds, which can be accomplished with specific IgE testing performed on a blood sample or through referral to a board-certified allergist for skin testing. Air sampling, thermography, moisture meters, environmental history, and direct observation are all useful techniques to identify moisture problems.…”
Section: Dampness and Moldmentioning
confidence: 99%